Between-hand difference in ipsilateral deactivation is associated with hand lateralization: fMRI mapping of 284 volunteers balanced for handedness - Tzourio-Mazoyer, N.; Petit, L.; Zago, L.; Crivello, F.; Vinuesa, N.; Joliot, M.; Jobard, G.; Mellet, E.; Mazoyer, B. (Frontiers in Human Neuroscience, 2015)
In right-handers, an increase in the pace of dominant hand movement results in increased ipsilateral deactivation of the primary motor cortex (M1). By contrast, an increase in non-dominant hand movement frequency is associated with reduced ipsilateral deactivation. This pattern suggests that inhibitory processes support right hand dominance in right-handers and raises the issues of whether this phenomenon also supports left hand preference in left-handers, and/or whether it relates to asymmetry of manual ability in either group. Thanks to the BIL&GIN, a database dedicated to the investigation of hemispheric specialization, we studied the variation in M1 activity during right and left finger tapping tasks in a sample of 284 healthy participants balanced for handedness. An M1 fMRI localizer was defined for each participant as an 8 mm diameter sphere centered on the motor activation peak. Right-handers exhibited significantly larger deactivation of the ipsilateral M1 when moving their dominant hand than their non-dominant hand. In contrast, left-handers exhibited comparable ipsilateral M1 deactivation during either hand movement, reflecting a bilateral cortical specialization. This pattern is likely related to left-handers’ good performances with their right hand and consequent lower asymmetry in manual ability compared with right-handers. Finally, inter-individual analyses over the whole sample demonstrated that the larger the difference in manual skill across hands, the larger the difference in ipsilateral deactivation. Overall, we propose that difference in ipsilateral deactivation is a marker of difference in manual ability asymmetry reflecting differences in the strength of transcallosal inhibition when a given hand is moving.